2009
DOI: 10.1111/j.1748-7692.2008.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of steroid hormones in whale blow: It is possible

Abstract: The feasibility of using analysis of hormone content of whale blow samples to assess reproductive function is addressed. A suitable collection method and analytical technique using liquid chromatography-mass spectrometry (LC-MS) has been developed. Blow samples were collected opportunistically from free-ranging humpback whales (Megaptera novaeangliae) (n = 35) and North Atlantic right whales (Eubalaena glacialis) (n = 18) using a 13-m carbon fiber pole with a collection device. Samples were analyzed for the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
108
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 50 publications
2
108
0
2
Order By: Relevance
“…To date, nylon (veil or stocking fabric) has been the most field-tested collection material for large whale blow (Hogg et al ., 2009; Hunt et al ., 2014a). However, more recent collection trials, using blow from captive cetaceans, demonstrated that nitex mesh had an improved performance in retaining sample volume (cf.…”
Section: Methodsmentioning
confidence: 99%
“…To date, nylon (veil or stocking fabric) has been the most field-tested collection material for large whale blow (Hogg et al ., 2009; Hunt et al ., 2014a). However, more recent collection trials, using blow from captive cetaceans, demonstrated that nitex mesh had an improved performance in retaining sample volume (cf.…”
Section: Methodsmentioning
confidence: 99%
“…However, some alternative sample types can be collected from whales, including feces, blubber biopsy dart samples, and respiratory vapor (e.g., Hogg et al, 2005Hogg et al, , 2009Hunt et al, 2006Hunt et al, , 2013Hunt et al, , 2014aKellar et al, 2006;Rolland et al, 2005;Vu et al, 2015). For example, fecal GCs of North Atlantic right whales (Eubalaena glacialis, NARW) show significant increases corresponding with energetically-demanding states such as pregnancy and lactation, as well as with anthropogenic stressors of chronic ocean noise and entanglement Hunt et al, 2006;Rolland et al 2005Rolland et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Besides whaling activities, well-known anthropogenic activities including fishery entanglement, chemical use/emission, environmental noise, ship strikes, and climate change are impacting whales, with evidence found through morphological or epidemiological analysis as well as chemical profiles from tissue, fecal, and exhalation samples (3)(4)(5)(6). However, we are currently unable to monitor and therefore assess the lifetime impacts of such anthropogenic pollution/activities on whales.…”
mentioning
confidence: 99%